Productos diferentes de la madera usados por la población de la comunidad nativa Santa Teresa II Zona, Rio Yavarí, Región Loreto - Diaz Coronado, Jhonn Keler (2024)
The present work was carried out in the Santa Teresa zone II community, Yavari river, Loreto region. To seek to identify the different products of wood, in order to have an alternative development in this area. The general objective was to know the forest species and their products other than wood and their uses. A survey format was used. 65 inhabitants grouped into 14 families were found. These families used timber products and non-timber products. 48 species were found such as: irapay, tambishe, huasai, aguaje, cacao, chuchuhuasi, guaba, caspi remo, chestnut, palisangre, cumaceba, oje, wambé, caimito, catahua, coconut, copal, granadilla, caspi milk, huayo milk, ubos, cat's claw, abuta, bacaba, capinuri, clove huasca, shapaja, topa, ungurahui, sacha garlic, sweets, sugar cane, casho, cedar, chambira, mango, pona, broom, sacha coriander, shimbillo, screw, grapefruit, umari, yarina, andiroba, bamboo, banana, cassava. Those who take advantage of the different species the most are Mr.: Apagueño Shahuano Gutember, Shahuano Atravera Carlos, with 19 species each, followed by Mr. Chota Curitimari Croiber with: 16 species and the other respondents with fewer species. The species with the highest percentage of uses are: Yrapay with (85.7%), Tambishi (85.7%) and Huasai with (71.4%) and the species with the lowest (7.14%) uses are: Ajo sacha, bonbonage, sugar cane, casho, cedar, chambira, mango, pona, broom, sacha cilantro, shimbillo, screw, grapefruit, umari, yarina, andiroba, bamboo, banana, yucca.